Clinicians’ view on non-adherence: sharing expert opinion - Tan, Ngiap Chuan; Joshi, Shashank R.; De-Madaria, Enrique; Mostafa, Badr Eldin; Özgirgin, O. Nuri; Simoncini, Tommaso; Tokgözoğlu, Lale (Frontiers in Pharmacology, 2025)
IntroductionMedication non-adherence (NA) remains a persistent challenge across all medical specialties, contributing to adverse patient outcomes and increased healthcare burdens. While numerous studies have explored patient-related factors influencing adherence, the perspectives of healthcare professionals remain underrepresented in literature. This study aims to document the individual experiences of seven international physicians across diverse medical fields, highlighting barriers, detection methods, and strategies employed to address NA in their daily practice.MethodologyA structured qualitative approach was employed, incorporating semi-structured interviews and written questionnaires to capture expert insights. Seven physicians from specialties including family medicine, gastroenterology, otolaryngology, otology and neurotology, obstetrics and gynecology, endocrinology and cardiology participated in the study. Data were analyzed thematically to identify recurring patterns, specialty-specific challenges, and practical solutions implemented by clinicians.ResultsClinicians reported that NA detection primarily relied on patient self-reporting, clinical markers, and medication reconciliation. Barriers to adherence varied by specialty but commonly included polypharmacy, treatment complexity, patient skepticism, socioeconomic constraints, and asymptomatic conditions. Strategies to enhance adherence encompassed patient education, shared decision-making, therapeutic simplification, digital tools, and team-based care models. Despite proactive efforts, clinicians cited systemic limitations such as time constraints, fragmented healthcare records, and inadequate adherence-tracking mechanisms.ConclusionAddressing NA requires a patient-centered, interdisciplinary approach integrating education, digital innovations, and structured follow-up strategies. The study underscores the necessity for larger-scale research to validate adherence interventions and refine multidisciplinary frameworks. Given the study’s qualitative nature and small sample size, future research should incorporate broader datasets and diverse healthcare perspectives to develop more comprehensive adherence solutions.